Effects of dry and wet coating methods on surface degradation of Ni-rich cathodes in Li-ion rechargeable batteries - Lee, Keonwoo; Jiang, Feng; Jeong, Seonghun; Lee, Hyojoo; Kim, Jung Ho; Mun, Junyoung (Frontiers in Batteries and Electrochemistry, 2025)
Ni-rich cathode materials have attracted significant attention as high energy density cathodes for lithium-ion batteries. However, Ni-rich cathode materials with a Ni content exceeding 80% have encountered challenges such as electrolyte side reactions due to the instability of Ni ions. These issues lead to rapid capacity fading and undermine battery stability. To address these problems, surface coating techniques have been widely employed. Among these methods, wet coating techniques have been commonly used. However, this approach leads to the unintended formation of a NiO-like phase due to water exposure, which accelerates cation mixing and degrades electrochemical performance. In this study, a dry coating method that excludes the influence of water was employed to enhance the surface stability of Ni-rich cathode materials. This enhanced stability is attributed to the suppression of NiO-like phase formation on the surface of the dry coated cathodes, which prevents cation mixing during cycling, avoids capacity degradation, and prolongs battery cycle life. Experimental results demonstrated significant differences between dry coated and wet coated Ni-rich samples based on LiNi0.8Co0.1Mn0.1O2 (NCM811). The capacity retentions of dry coated and wet coated NCM811 at 0.5C at 150 cycles were 80.8% and 73.4%, respectively. This result demonstrates that dry coating offers a statistically significant improvement in long-term capacity retention, reflecting a 10% enhancement in stability compared to conventional methods. Rate capability was evaluated by cycling at incremental rates from 0.2C to 20C (3 cycles per rate) followed by an additional 150 cycles at 0.5C. The results demonstrated that the dry coated sample exhibited a more pronounced and stable rate capability across all tested conditions compared to the wet coated sample. These findings confirm that the absence of NiO-like phase formation contributed significantly to enhancing the electrochemical performance, particularly in terms of stability and long-term reliability.